Assessment of renal and hepato-protective potential of guava leaves in male Sprague dawley rats - Nasir, Makia; Tahir-Nadeem, Muhammad; Saeed, Farhan; Ahmad, Tanvir; Imran, Muhammad (Cellular and Molecular Biology, 2021)
Present research project was an attempt to explore the functional/nutraceutical worth of guava leaves from two locally grown varieties (Ruby & Safeda). For the purpose, guava leaves extract was fed to experimental male Sprague Dawley rats to explore the nutraceutical potential of guava leaves against hepatotoxicity. Two studies were performed on two types of rats i.e. study I (normal rats), study II (hepatotoxic rats). In both studies, 250 mg/kg each of pink guava leaves extracts (T1) and white guava leaves extracts (T2) was added in the feed. Feed intake and body weights of the rats were recorded. At the end of the first and eighth week of study, the blood samples of the rats were analyzed to check the effect of guava leaves extracts on renal functioning (Alkaline Phosphatase, Alanine Transaminase and Aspartate Transaminase) as well as liver functioning parameters including urea and creatinine. In both studies, comparatively higher feed consumption was observed in the control group than the rest of the treatments. At the end of study I, the highest weight (207±9.21 g) was observed in T0 whereas, during study II, the maximum value (202±5.58 g) was found in T2 (rats consuming white guava leaves extract) that indicates its effectiveness against hepatotoxicity. Regarding renal functioning tests, pink guava leaves were more effective in decreasing urea and creatinine levels in rats as compared to the white guava leaves in both study plans. Likewise, in each of study trial, pink guava leaves were more effective in reducing AST, ALT and ALP than white guava leaves and control. From the present investigation, it is deduced that guava leaves were effective against hepatotoxicity.